Short-Term Wind Speed Forecasting With Deep Learning - Karaaslan, Fatih; Alçin, Zeynep Mine; Aslan, Muzaffer (Fırat Üniversitesi, 2025)
Wind speed forecasting is crucial for planning and investing in renewable wind energy. In addition, Wind speed forecasting is essential for planning renewable wind energy, optimizing wind power production, and enhancing transmission line capacities. However, intermittent and stochastic fluctuations of wind speed pose a significant problem for high quality wind speed forecasting. In this study, a deep learning-based approach is proposed for wind power plant planning and feasibility studies that can provide wind speed prediction more easily. In this approach, firstly, wind speed time data were converted into color images using continuous wavelet transform. The obtained images were applied to the pre-trained AlexNet CNN model and wind speed prediction was performed. In the study, hourly speed data from the Elazig meteorology regional directorate between 2018-2019 were used. In the experimental studies, three different horizon forecasts were made: 1-hour, 2-hour and 3-hour. Metrics like correlation coefficient (R), mean absolute error (MAE), and root means square error (RMSE) were utilized to assess the proposed forecasting models performance. In the experimental studies, the whole dataset images were randomly divided into three parts as training, validation and test at the rates of 70%, 10% and 20% respectively for transfer learning. In the 1-hour horizon forecast, the best wind speed prediction was achieved with experimental results of 0.0335, 0.0275 and 0.9517 for RMSE, MAE and R metrics, respectively. In this respect, the proposed AlexNet model shows that it is an effective model in wind speed forecast since the 1-hour horizon forecast is more reliable and accurate.

Rüzgar hızı, yenilenebilir rüzgar enerjisine yatırım yapılması ve planlanmasında rüzgar hızının tahmin edilmesi hayati önem taşımaktadır. Ayrıca mevcut rüzgar santrallerinin üretimi ve iletim hatlarının kapasitelerinin artırılmasında da rüzgar hızının tahmin edilmesi oldukça önem arz etmektedir. Fakat rüzgar hızının aralıklı ve stokastik dalgalanmaları, yüksek kaliteli rüzgar hızı tahmini için önemli bir sorun oluşturmaktadır. Bu çalışmada, rüzgar santrallerinin planlanması ve uygulanabilirlik çalışmaları için rüzgar hız tahminini daha kolay sağlayabilecek derin öğrenme temelli bir yaklaşım önerilmiştir. Bu yaklaşımda öncelikle rüzgar hız zaman verileri sürekli dalgacık dönüşümü ile renkli görüntüye dönüştürüldü. Elde edilen görüntüler, önceden eğitilmiş AlexNet CNN modeline uygulanarak rüzgar hız tahmini gerçekleştirilmektedir. Çalışma, Elazığ meteoroloji bölge müdürlüğünden alınan 2018-2019 yılları arasındaki saatlik hız verileri kullanılmıştır. Yapılan deneysel çalışmalarda, 1-saat, 2-saat ve 3-saat olmak üzere üç farklı ileri ufuk tahmini yapılmıştır. Önerilen tahmin modelinin modelin performans değerlendirilmesi için ortalama mutlak hata (MAE), ortalama karekök hatası (RMSE) ve korelasyon katsayısı (R) metrikleri kullanılmıştır. Deneysel çalışmalarda, tüm veri seti görüntüleri transfer öğrenimi için rastgele bir şekilde sırasıyla %70, %10 ve %20 oranlarında eğitim, doğrulama ve test olmak üzere üç bölüme ayrılmıştır. 1-saat ileri tahminde RMSE, MAE ve R metrikleri için sırasıyla 0,0335, 0,0275 ve 0,9517 deneysel sonuçlar ile en iyi rüzgar hız tahmini gerçekleştirilmiştir. Bu bakımdan önerilen AlexNet modelinde, 1 saat ileri tahmininde, daha güvenilir ve doğru tahmin gerçekleştirdiğinden rüzgar hız tahmininde etkili bir model olduğunu göstermektedir.
Derin Öğrenme ile Kısa Vadeli Rüzgar Hız Tahmini
Keywords: Electrical Engineering (Other); Elektrik Mühendisliği (Diğer)